Effect of hydrogen injection into natural gas on the mechanical strength of natural gas pipelines during transportation (Archives of Mechanics - Test, 2014)
The aim of this paper is to study the effect of hydrogen injection into natural gas transient flows on the mechanical strength of natural gas pipelines. The governing equations of hydrogen-natural gas mixtures are two nonlinear partial differential equations. The fluid pressure and velocity are considered as two principal dependent variables. The fluid is a homogeneous hydrogen-natural gas mixture for which the density is defined by an expression averaging the two gas densities where an adiabatic process is admitted for the two components. The problem has been solved by the nonlinear method of characteristics. By the use of Laplace’s law, the pipe’s circumferential stress has been analyzed for different hydrogen mass fraction in the mixture. It was then compared to the allowable stress of different grade pipeline steels used to transport natural gas. The obtained results have shown that the allowable stress for the natural gas pipelines is exceeded for some fractions of hydrogen in the hydrogen-natural gas mixtures.